Giant cell temporal arteritis: a clinicopathological study with emphasis on unnecessary biopsy - Alkatan, Hind M.; AlMana, Fawziah; Maktabi, Azza M. Y. (Frontiers in Ophthalmology, 2023)
Introduction Temporal artery (TA) biopsy is commonly used for the diagnosis of giant cell arteritis (GCA). However, a positive biopsy is no longer mandatory for diagnosis. This study aims to correlate the histopathological findings of TA biopsies in suspected cases of GCA to the clinical presentation in an ophthalmic tertiary eye care center to draw useful conclusions and advocate the possible implementation of guidelines for TA biopsy. Methods Data was collected from patients’ medical records including, demographics, clinical data, and histopathological findings and diagnosis. The 2022 American College of Rheumatology/ European Alliance of Associations for Rheumatology (ACR/EULAR) criteria have been used and partially adopted as a guide to compare the variables between TA biopsy-positive and negative groups as well as the TA biopsy-positive group and the group of patients with TA biopsy showing atherosclerosis. Results Out of the total 35 patients who underwent a TA biopsy during the period of 23 years, 22.9% of patients had histopathological findings consistent with GCA and 42.9% had TA atherosclerotic changes, while the remaining 34.3% had histologically unremarkable TA. The mean age of all patients was 66 ± 10.9 years. Slightly more than half were females (54.3%) and the remaining were males (45.7%). In the group with positive TA biopsies, the mean age was 71 ± 8.4 years with a higher female predominance (female-to-male ratio of 5:3). The mean diagnostic clinical score used in our study was higher (7.5 ± 2.33) in the GCA-positive group when compared to the other groups with statistical significance (mean of 4.85 ± 2.01 in patients with overall GCA-negative biopsies and 5.13 ± 2.10 in the group with atherosclerosis). Other three clinical variables that were found to be statistically significant in the GCA biopsy-positive group were scalp tenderness, jaw claudication, and optic nerve pallor. Discussion The mean age (71 ± 8.4 years) and the female predominance of GCA in our group of patients with positive TA biopsy (62.5%) was like other reports. In our study 22.9% of performed TA biopsies over the period of the study were positive confirming the diagnosis of GCA on histological exam, which was similar to another report and is considered to be relatively low. The incorporation of increased clinically focused assessments and algorithms, with the aid of the ACR/EULAR criteria, may decrease the frequency of TA biopsies that carries unnecessary cost and risk of procedure-related morbidity. We highly recommend applying the age of ≥ 50 years as an initial criterion for diagnosis, followed by the consideration of the statistically significant clinical features: scalp tenderness, jaw claudication, and optic nerve pallor.